Chemical composition and in vitro antifungal activity of Zingiber officinale essential oil against foodborne pathogens isolated from a traditional cheese wagashi produced in Benin - FAROUGOU, SOUAÏBOU; SESSOU, PHILIPPE; NOUDOGBESSI, JEAN PIERRE AKODOGBO; FANOU, BRICE; AZOKPOTA, PAULIN; YOUSSAO ABDOU KARIM, ISSAKA; SOHOUNHLOUE, KOKO CODJO DOMINIQUE (My University, 2012)
The aim of the present work was to assess some antifungal activity parameters as mycelial growth inhibition, minimum inhibitory concentration (MIC) and minimum fungicidal concentration (MFC) of Zingiber officinale essential oil from Benin against Aspergillus (flavus and tamarii), Fusarium (poae and verticillioides) and Penicillium (citrinum and griseofulvum) species isolated from traditional cheese wagashi. The chemical composition of the essential oil extracted by hydrodistillation with Clevenger apparatus from fresh rhizomes of ginger was studied by GC-FID and GC-MS and showed -zingiberene (40.7%) as major component with minor compounds in significant percents such as geranial (8.9%), elemol (5.9%), neral (4.5%), camphor (4.3%), limonene (3.7%) and (E, E)-α-farnesene (3.6%). The evaluation of antifungal activity of this oil has shown a less activity against all the species tested with mycelia growth inhibition not exceeding 79.66% excepted Penicillium griseofulvum on which the oil had fungistatic activity with MIC equal to 1000 mg/L. Results obtained in the present study reveal that Zingiber officinale essential oil is not a good antifungal agent against moulds species responsible for wagashi deterioration. Its activity may be improved by its combination with other natural active products.
Keywords: Zingiber officinale; volatile extract; antifungal activity; wagashi